Cardiac involvement in Erdheim-Chester disease: a case report. - Pivatto Júnior, Fernando; Piardi, Diogo Silva; Torres, Felipe Soares (Clinical and Biomedical Research, 2015)
Erdheim-Chester disease (ECD) is a rare non-Langerhans cell histiocytosis of unknown etiology characterized by proliferation of lipid-containing foamy histiocytes affecting bones and potentially every organ. There is a wide clinical spectrum of the disease, ranging from asymptomatic bone or soft-tissue lesions to life-threatening systemic involvement. Although the initial descriptions published by Jakob Erdheim and William Chester in 1930 included a patient with right atrial infiltration on autopsy, cardiovascular involvement in ECD has only gained more recognition recently. In the present report, we describe a case with cardiac involvement, presenting with symptomatic heart failure and a cardiac mass assessed with echocardiogram and cardiac magnetic resonance imaging.